2015
DOI: 10.5268/iw-5.4.804
|View full text |Cite
|
Sign up to set email alerts
|

Testing and application of a two-dimensional hydrothermal/transport model for a long, deep, and narrow lake with moderate Burger number

Abstract: Setup, testing, and application of a 2-dimensional longitudinal-vertical hydrothermal/transport model (the transport submodel of CE-QUAL-W2) was documented for Cayuga Lake, New York, where the Rossby radius is on the order of the lake's width. The model was supported by long-term monitoring of meteorological and hydrologic drivers and calibrated and validated using in-lake temperature measurements made at multiple temporal and spatial scales over 16 years. Measurements included (1) temperature profiles at mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…The mean water age values we simulated for the bays of Lake George fall in the same order of magnitude as the residence time (3.5 days) that was simulated in the shelf area of the main basin of Cayuga Lake, NY, by Gelda et al (2015) and by Rueda et al (2008) who found the transfer of tracers from a bay of Clear Lake, CA, to the main basin required 7 days. Although, water age and residence time are different time scales, Rayson et al (2016) showed similarities between the two time scales in their study of Galveston Bay, Texas, and past studies have assumed water age to be similar to residence time (Duffy et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…The mean water age values we simulated for the bays of Lake George fall in the same order of magnitude as the residence time (3.5 days) that was simulated in the shelf area of the main basin of Cayuga Lake, NY, by Gelda et al (2015) and by Rueda et al (2008) who found the transfer of tracers from a bay of Clear Lake, CA, to the main basin required 7 days. Although, water age and residence time are different time scales, Rayson et al (2016) showed similarities between the two time scales in their study of Galveston Bay, Texas, and past studies have assumed water age to be similar to residence time (Duffy et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…It has the second largest surface area (172 km 2 ) and volume (9.4 × 10 9 m 3 ) of this group of lakes, with mean and maximum depths of 55 m and 133 m, respectively (Schaffner and Oglesby ). This alkaline hardwater, mesotrophic lake (Effler et al ) has an average residence time of 5.5 yr (Gelda et al ). Nearly 40% of the total tributary inflow from three of the largest streams enters the southern end of the lake.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the models resolve the vertical and one horizontal (longitudinal) dimension -2DV, suitable for elongated deep-water bodies where vertical thermal stratification plays a major role, e.g. CE-QUAL-W2 (Gelda et al, 2015;Kobler et al, 2018;Mi et al, 2020). Finally, three-dimensional (3D) models provide highly detailed spatial 45 data, but require larger computational effort in terms of time and storage.…”
Section: Introductionmentioning
confidence: 99%